Herpes simplex virus 1 glycoprotein C promotes virus penetration from endosomes during entry, independent of interaction with heparan sulfate - Seth M. Schneider; Seth M. Schneider; Giulia Tebaldi; Katrina A. Gianopulos; Katrina A. Gianopulos; Darin J. Weed; Suzanne M. Pritchard; Chloe Leach; Anthony V. Nicola; Anthony V. Nicola (Frontiers in Microbiology)
Herpes simplex virus 1 (HSV-1) gC is a multi-functional glycoprotein present in the viral envelope and on the surface of infected cells. Virion gC, and to a lesser extent the fusion protein gB, interacts with host heparan sulfate to mediate HSV-1 attachment to the cell surface. Virion gC selectively facilitates HSV-1 entry into cells that support entry by a low pH-dependent endocytic pathway. gC regulates fusion-associated conformational changes in gB. Here we investigated the mechanism by which gC plays a post-attachment role in HSV-1 entry into cells. HSV-1 entered HS-deficient cells by a low pH-dependent route. Similarly, HSV-1 deleted for HS-binding domains entered HS-bearing cells by a low pH pathway. Thus, the presence of HS on cells and the ability of HSV-1 to engage HS do not direct HSV-1 to a pH-dependent entry pathway. HSV-1 lacking gC accumulated in endosomes during viral entry, supporting the notion that gC influences viral penetration from endosomes. Interestingly, the pH-neutral cell–cell fusion mediated by HSV-1 glycoproteins gB, gD, and gH/gL was not altered by gC. Soluble heparin inhibited cell–cell fusion regardless of the presence of gC or heparan sulfate. The kinetics of endocytic uptake of gC-null HSV-1 was rapid and very similar to wild type virus. Thus, the role of gC in regulating low pH entry of HSV-1 occurs downstream of internalization of enveloped particles from the plasma membrane. Together, the results presented here and elsewhere support a post-attachment, post-internalization function for gC in HSV-1 entry that is independent of HS.